Obstructive sleep apnea related to rapid-eye-movement or non-rapid-eye-movement sleep: comparison of demographic, anthropometric, and polysomnographic features - Sunnetcioglu,Aysel (2016)
Objective : To determine whether there are significant differences between rapid-eye-movement (REM)-related obstructive sleep apnea (OSA) and non-REM (NREM)-related OSA, in terms of the demographic, anthropometric, and polysomnographic characteristics of the subjects. Methods : This was a retrospective study of 110 patients (75 males) with either REM-related OSA (n = 58) or NREM-related OSA (n = 52). To define REM-related and NREM-related OSA, we used a previously established criterion, based on the apnea-hypopnea index (AHI): AHI-REM/AHI-NREM ratio > 2 and ≤ 2, respectively. Results : The mean age of the patients with REM-related OSA was 49.5 ± 11.9 years, whereas that of the patients with NREM-related OSA was 49.2 ± 12.6 years. The overall mean AHI (all sleep stages combined) was significantly higher in the NREM-related OSA group than in the REM-related OSA group (38.6 ± 28.2 vs. 14.8 ± 9.2; p < 0.05). The mean AHI in the supine position (s-AHI) was also significantly higher in the NREM-related OSA group than in the REM-related OSA group (49.0 ± 34.3 vs. 18.8 ± 14.9; p < 0.0001). In the NREM-related OSA group, the s-AHI was higher among the men. In both groups, oxygen desaturation was more severe among the women. We found that REM-related OSA was more common among the patients with mild-to-moderate OSA, whereas NREM-related OSA was more common among those with severe OSA. Conclusions : We found that the severity of NREM-related OSA was associated mainly with s-AHI. Our findings suggest that the s-AHI has a more significant effect on the severity of OSA than does the AHI-REM. When interpreting OSA severity and choosing among treatment modalities, physicians should take into consideration the sleep stage and the sleep posture.